Nathan Lyons: In Pursuit of Magic at the George Eastman Museum (Rochester, NY), retrospective or exhibition? - Bruno Chalifour (Transatlantica)
Nathan Lyons (1930 – 2016) lived in Rochester NY from 1957 to his death. He was a curator then an assistant director of the George Eastman Museum (1957 – 1969), working with Beaumont Newhall and Minor White, the co-founder of the Society for Photographic Education (1963) and Oracle (international conference of photo historians and curators since 1983), the founder of Visual Studies Workshop (1969) and its magazine (Afterimage, 1972 – 2018), and a consultant for the National Endowment for the Arts and the New York Foundation for the Arts (president 1976 – 1991). Before being a curator, an educator, a theorist (among others, the snapshot esthetic, the social landscape, sequences & series, the photo-book), an advocate for visual literacy, and a key-figure in post-WWII American photography, he was a photographer-artist who looked at urban America with a sometimes amused, sometimes critical eye. Whereas Lyons photographed in black-and-white for over fifty years, a great space in this exhibition was dedicated to his recent digital color work. His curating, writings and photographs have challenged and expanded the medium in many ways (ICP Infinity Award for Lifetime Achievement in 2000), was he, with his latest work, achieving the same goals?